2018
DOI: 10.1302/1863-2548.12.170155
|View full text |Cite
|
Sign up to set email alerts
|

Clavicle fracture nonunion in the paediatric population: A systematic review of the literature

Abstract: AimsClavicle fracture nonunions are extremely rare in children. The aim of this systematic review was to assess what factors may predispose children to form clavicle fracture nonunions and evaluate the treatment methods and outcomes.MethodsWe performed a systematic review according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, aiming to find papers reporting clavicle fracture nonunion in children under the age of 18 years. Data was collected on patient demographics, fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…The exact pathophysiological reason for such a connection is not further elaborated nor known, yet Smith and William identify the fact that many subclinical congenital pseudoarthrosis may not be identified or visible on X-ray nor by physical exam. This may lead to a lack of pathology recognition, thus predisposing such patients to a line of weakness in the case of trauma, leading to fracture at this pseudoarthritic site and subsequent misdiagnosis as a "posttraumatic nonunion" [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact pathophysiological reason for such a connection is not further elaborated nor known, yet Smith and William identify the fact that many subclinical congenital pseudoarthrosis may not be identified or visible on X-ray nor by physical exam. This may lead to a lack of pathology recognition, thus predisposing such patients to a line of weakness in the case of trauma, leading to fracture at this pseudoarthritic site and subsequent misdiagnosis as a "posttraumatic nonunion" [5].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of nonunion in the paediatric population is extremely rare, in contrast to that known of the adult population, where the rate is from 8% to 14% [4]. A systematic review undertaken by Hughes et al reported 21 paediatric cases of nonunion, the majority of which occurred after a displaced right-sided fracture and with typical presentation occurring at a distance of one year [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fractures on the left side (58%) and on the non-dominant side (56%) are slightly more common [ 4 ]. Most clavicle fractures occur in the middle section of the bone, accounting for 70% to 95% of all pediatric clavicle fractures [ 1 , 5 , 6 ]. Displaced fractures of the clavicle are relatively common, ranging from 28% to 67% of all clavicle fractures in children and adolescents [ 1 , 4 , 6 , 7 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…• Clavicle fractures represent 95% of fractures seen during childbirth while passing through the birth canal [24].…”
Section: Incidencementioning
confidence: 99%